The French Revolution : a very short introduction - Doyle, William, 1942- (Oxford University Press : [s.n.], 2001)
A brief introduction to the French Revolution that explores the impact the French Revolution had on literature, society, and institutional and social structures in France and beyond.
Includes bibliographical references (p. 119-123) and index.
Adult
Keywords: France -- History -- Revolution, 1789-1799.; France -- History -- 1789-1799, Revolution